Three-dimensional MR coronary angiography using the navigator technique compared with conventional coronary angiography. - Sandstede, J; Pabst, T; Beer, M; Geis, N; Kenn, W; Neubauer, S; Hahn, D (1999)
OBJECTIVE: We evaluated the diagnostic accuracy of three-dimensional (3D) MR coronary angiography with the navigator technique for the detection of coronary artery stenoses in comparison with that of conventional radiographic angiography. SUBJECTS AND METHODS: Thirty patients with coronary artery disease were examined with an ECG-triggered 3D fast low-angle shot sequence using retrospective respiratory gating and the navigator technique on a 1.5-T MR scanner. The data set was evaluated as a 3D view with a surface rendering technique. RESULTS: Imaging of the proximal coronary arteries was possible in all patients. The average visualized lengths of the left main, left anterior descending, left circumflex, and right coronary arteries were 1.9+/-0.5 cm (mean +/- SD), 5.2+/-2.3 cm, 4.2+/-1.9 cm, and 5.2+/-2.5 cm, respectively. Irregular breathing reduced image quality in seven of the 30 patients, making diagnosis of stenoses impossible. In the 77% of patients whose examinations resulted in high-quality images, the sensitivity and specificity for detection of significant stenoses and occlusions in all four main coronary arteries were 81% and 89%, respectively. CONCLUSION: The navigator technique allows reproducible imaging of the proximal course of coronary arteries. This technique obviates breath-hold studies, thus allowing more patients to be examined. In patients whose examinations resulted in high-quality images, significant coronary artery lesions could be seen. However, for widespread clinical use, further technical improvement is necessary to increase sensitivity and specificity.